Evaluating the Effects of Colonization with Multidrug-Resistant Bacteria on the Outcomes of Induction Chemotherapy in Patients with Acute Leukemia: A Prospective Analysis - Perraju Bhaskar Bhuvan Lagudu; Varalakshmi Vijaykumar; Mounica Chekuri; Devleena Gangopadhyay; Jayachandran Perumal Kalaiyarasi; Prasanth Ganesan; Swaminathan Rajaraman; Venkatraman Radhakrishnan (Indian Journal of Medical and Paediatric Oncology)
Introduction The presence of multi-drug resistant (MDR) bacteria has been linked to higher rates of morbidity and mortality in patients with acute leukemia.